2017
DOI: 10.1186/s13014-017-0866-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of photon volumetric modulated arc therapy, intensity-modulated proton therapy, and intensity-modulated carbon ion therapy for delivery of hypo-fractionated thoracic radiotherapy

Abstract: PurposeThe aim of the present study was to compare the dose distribution generated from photon volumetric modulated arc therapy (VMAT), intensity modulated proton therapy (IMPT), and intensity modulated carbon ion therapy (IMCIT) in the delivery of hypo-fractionated thoracic radiotherapy.Methods and materialsTen selected patients who underwent thoracic particle therapy between 2015 and 2016 were re-planned to receive a relative biological effectiveness (RBE) weighted dose of 60 Gy (i.e., GyE) in 15 fractions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The additional benefit that carbon ions have, over other charged particles like protons, is an increased biological effectiveness because of dense ionization and the resulting complex DNA damage . Carbon ion treatment can also improve tumor control without increasing toxicity and is considered a radical nonsurgical therapy that achieves high local control rates without severe adverse effects . Charged particle therapy, especially with carbon ions, is known to be effective for various treatment sites including lung and may even be a safer option than photon SBRT and protons in case of large or central tumors and poor pulmonary function …”
Section: Introductionmentioning
confidence: 99%
“…The additional benefit that carbon ions have, over other charged particles like protons, is an increased biological effectiveness because of dense ionization and the resulting complex DNA damage . Carbon ion treatment can also improve tumor control without increasing toxicity and is considered a radical nonsurgical therapy that achieves high local control rates without severe adverse effects . Charged particle therapy, especially with carbon ions, is known to be effective for various treatment sites including lung and may even be a safer option than photon SBRT and protons in case of large or central tumors and poor pulmonary function …”
Section: Introductionmentioning
confidence: 99%
“…Studies on IMCT remain limited. Chi et al compared the dose distribution of IMCT, IMPT, and volumetric modulated arc therapy in thoracic radiotherapy (17). They found no significant difference in PTV coverage between the three modalities, and IMCT was able to reduce low-dose areas in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike single field uniform dose (SFUD) irradiation, which irradiates uniform doses with each beam, IMCT is an irradiation method in which the individual beams are irradiated at non-uniform doses and the total dose is equalized by the sum of the individual beams (16). Several dosimetric studies have reported that good dose distribution can be obtained with IMCT (17,18). Furthermore, reports on the clinical application of IMCT are limited, and results of IMCT in head and neck cancer have been reported (19,20).…”
mentioning
confidence: 99%
“…Further, the literature is replete with studies that explored the superior conformity and theoretical radiobiological advantages of carbon ion therapy regarding tumor control (Weber et al 2009, Grun et al 2015, Dokic et al 2016, Chi et al 2017. It has also been suggested that conformity is even more important in treatments with dose escalation (Mohamad et al 2017, Malouff et al 2020.…”
Section: Introductionmentioning
confidence: 99%